1 ecuacion equivalente a -9x+12y=36 a) x=4+4/3y b) x= -4+4/3y c) y= x+3+3/4x d) y= 3-3/4x 2 ecuacion equivalente a 1/2x-2y=4 a) y=2-2x b) y= -2+1/4x c) x= 4y+4y 3 ecuacion equivalente a -3x-1/3y=9 a) y= -27-9x b) y= -3-x c) x= 1/9y=3 d) x= -3x-1/3y=9 4 ecuacion equivalente a -2x+6y=12 a) x=2+1/3y b) x= -6+3y c) y= 1/3x+2 d) y= 3x-6 5 ecuacion equivalente a 1/5x-1/5y= -1 a) y= 5-x b) y=5+x c) x=y+5 d) x= y-5 6 ecuacion equivalente a 0.2x + 0.5y a) x=5-4y b) y= 1.25-0.25x c) x=0.2-.16y d) y=0.5-0.16x